Root causes of deaths by suicide among patients under the care of a mental health trust: thematic analysis. (June 2021) - Odejimi, Opeyemi; Webb, Kerry; Bagchi, Dhruba; Tadros, George
Abstract : Aims and method: This study explored the root causes of deaths by suicide among patients under the care of a mental health trust. Thematic analysis was carried out to identify themes from the serious incident reports for patients between 1 January 2017 and 31 July 2018. Results: In total, 48 cases were reviewed. Three main themes emerged from this study: patient-, professional- and organisation-related factors. The majority of the deaths were caused by patient-related factors, particularly exacerbation of the patient's mental health condition. Clinical implications: This study provides insight into perceived causes of death by suicide among mental health patients. It is hoped that this will, in turn, influence the manner in which decisions, policies and resource allocation are carried out to further prevent and reduce the incidence of suicide, particularly among mental health patients.